The Effects of International Trade Openness on Government Revenue: Empirical Evidence from Middle East and North African Region Countries - Shubita, Rawan F.; Warrad, Taleb Awad (International Journal of Economics and Financial Issues, 2018)
This study investigates the impact of international trade openness on government revenue in Middle East and North African (MENA) countries for the period of 2000-2015. More specifically, this study examines the relationship between government revenue and international trade openness, real gross domestic product (GDP) per capita, corruption level measure, and population. The study utilized panel data, covering the period of 2000-2015, for nine selected MENA countries. The results of the study, using the panel fully modified least squares, highlights the negative impact of international trade openness on government revenue. Moreover, the results indicate that countries with a higher real GDP per capita and lower corruption level have more government revenue while the total population plays a negative role in government revenues. Keywords: Trade Liberalization, Government Revenue, Gross Domestic Product JEL Classifications: E01, F1, H5